Stress in telephone helpline nurses is associated with failures of concentration, attention and memory, and with more conservative referral decisions. - Allan, Julia L.; Farquharson, Barbara; Johnston, Derek W.; Jones, Martyn C.; Choudhary, Carolyn J.; Johnston, Marie (British Journal of Psychology, 2014)
Nurses working for telephone-based medical helplines must maintain attentional focus while quickly and accurately processing information given by callers to make safe and appropriate treatment decisions. In this study, both higher levels of general occupational stress and elevated stress levels on particular shifts were associated with more frequent failures of attention, memory, and concentration in telephone nurses. Exposure to a stressful shift was also associated with a measurable increase in objectively assessed information-processing errors. Nurses who experienced more frequent cognitive failures at work made more conservative decisions, tending to refer patients on to other health professionals more often than other nurses. As stress is associated with cognitive performance decrements in telephone nursing, stress-reduction interventions could improve the quality and safety of care that callers to medical helplines receive.